Les élevages pour questionner la relation à l’animal avec des élèves de maternelle - Raphaël Chalmeau; Monique Lafitole; Sophie Mourgues; Maéva Ramos Béato; Gabrielle Bergamaschi; Lucile Mortelecque; Dorothée Sales-Hitier (Recherches en Éducation)
From kindergarten onwards, raising animals in the classroom is particularly appropriate for building an observational approach and for developing a sense of responsibility towards animals. The relationship between humans and non-humans is a renewed research theme in view of contemporary issues related to the place of humans in the living world and the protection of biodiversity. This question lies at the interface of scientific learning in schools, the inclusion of the affective dimension in this learning, and the acquisition of a sense of responsibility towards the living world. We present the results of a collaborative research conducted in four multi-age kindergarten classes on the construction of a relationship with animals. The data are based on interviews with pupils to collect their perceptions of the animal (ante and post interviews) and on a discussion about animal care. Data analysis enables us to identify the nature of relationships with animals through the involvement of affective, cognitive and moral dimensions. We discuss the value of developing interspecific empathy and its contribution to the construction of an ethical posture towards non-human animals.